Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1021/np50094a006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ergobine, a New Natural Peptide Ergot Alkaloid

Abstract: The isolation and structure elucidation of a new ergot peptide alkaloid, ergobine [1], from submerged cultures of Claviceps purpurea strain 231 FI, are described. Its purification and identification were achieved by feeding experiments with a labelled precursor.FEEDING experiments.-[ 1 -uC]-Aminobutyric acid (Amersham, GB) (250 µ-Ci, 9.25 MBq) was fed to a seven-day-old 50 ml submerged culture of C. purpurea 231 FI (ATCC 20106). Medium and experimental 'Present address: Pharmaton, 6934 Bioggio (Switzerland).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…(Whichever was the ancestral ergopeptine cannot be discerned from the available data.) Remarkably, LpsA neofunctionalization appears to have accelerated dramatically in the Claviceps clade to give vast majority of known ergopeptines shown in Figure 3 (Blaney et al 2003; Cvak et al 1994, 1996, 2005; Eleuterius and Meyers 1977; Komarova and Tolkachev 2001; and references therein; Perellino et al 1993). …”
Section: Evolution Of Ergot-alkaloid Biosynthetic Pathwaysmentioning
confidence: 99%
“…(Whichever was the ancestral ergopeptine cannot be discerned from the available data.) Remarkably, LpsA neofunctionalization appears to have accelerated dramatically in the Claviceps clade to give vast majority of known ergopeptines shown in Figure 3 (Blaney et al 2003; Cvak et al 1994, 1996, 2005; Eleuterius and Meyers 1977; Komarova and Tolkachev 2001; and references therein; Perellino et al 1993). …”
Section: Evolution Of Ergot-alkaloid Biosynthetic Pathwaysmentioning
confidence: 99%
“…The known "ergot alkaloids" produced by Clauiceps spp. may be divided into five major classes: the clavine, lysergic acid, simple lysergic acid amides, ergopeptine, and ergopeptam alkaloids (Berde and Schild, 1978;Perellino et al, 1992Perellino et al, , 1993. The ergopeptines, simple lysergic acid amides, and clavines (Figures 1, 5, and 6 ) have been isolated from A. coenophialum-infected tall fescue (Yates et al, 1985;Lyons et al, 1986;Petroski and Powell, 1991).…”
Section: A Coenophialum-infected Fescuementioning
confidence: 99%
“…The major advantages of TLC are that several samples may be analyzed at the same time, TLC does not involve expensive instrumentation, and it may be used as a complement to MS in the confirmatory identification and analysis of mixtures of epimeric alkaloids (see below). Perellino et al (1993) have reported a TLC procedure on silica gel for the separation of most all of the known ergot alkaloids. By developing the TLC plates in methylene chloride: isopropyl alcohol (92:8, vol/vol) three times (drying the plates between runs), these alkaloids separate into the isolysergic acid group (i.e., -inine epimers), the ergotoxine group, the ergoxine group, and a mixture of the ergotamine and clavine groups.…”
Section: A Coenophialum-infected Fescuementioning
confidence: 99%
See 1 more Smart Citation
“…These assignments were confirmed by long-range 1 H− 13 C correlation of the α-protons with both β- and γ-carbons and the correlations of the N -H with the α-carbon in each residue. Configurations of the remaining asymmetric centers, as shown, are the same as for the regular series of ergopeptines; however, absolute configurations at the 2‘, 5‘, 8‘, and 9‘ positions of 1 remain to be determined.…”
mentioning
confidence: 99%